2021
DOI: 10.1002/nafm.10557
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Two Techniques for Remediation of Lacustrine Rocky Reef Spawning Habitat

Abstract: Rocky reef habitats in lacustrine systems constitute important areas for lithophilic-spawning fishes. Interstitial spaces created by the structure of rocky reefs form microenvironments where incubating embryos and juvenile fish are potentially protected from predators and physical displacement. However, if interstitial spaces are filled or blocked by sediment or biofouling, the reef structure may lose these benefits. Common practices to restore reef habitat include augmentation of existing reef structures or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…These devices were small in scale (1.35 m × 1.0 m; <90 kg) and were able to be towed by a smaller research vessel (6.4 m long). Results showed that both cleaning devices were able to successfully increase the relative hardness of the bottom substrate in some sampling areas, suggesting that the cleaning devices have the potential to remove sediments from rocky spawning reefs [58]. Furthermore, removal of sediments and increases in relative hardness over cleaned areas of the reef resulted in increased egg deposition by walleye and lake whitefish in these areas.…”
Section: Novel Remediation Techniquesmentioning
confidence: 96%
See 2 more Smart Citations
“…These devices were small in scale (1.35 m × 1.0 m; <90 kg) and were able to be towed by a smaller research vessel (6.4 m long). Results showed that both cleaning devices were able to successfully increase the relative hardness of the bottom substrate in some sampling areas, suggesting that the cleaning devices have the potential to remove sediments from rocky spawning reefs [58]. Furthermore, removal of sediments and increases in relative hardness over cleaned areas of the reef resulted in increased egg deposition by walleye and lake whitefish in these areas.…”
Section: Novel Remediation Techniquesmentioning
confidence: 96%
“…Fine sediment removal methods were recently tested in lentic environments using two benthic sled devices that utilized either pressurized water or propulsion-driven water to clear sediments and other fouling from the interstitial spaces of two rocky spawning reefs in Saginaw Bay, Lake Huron, USA [58]. These devices were small in scale (1.35 m × 1.0 m; <90 kg) and were able to be towed by a smaller research vessel (6.4 m long).…”
Section: Novel Remediation Techniquesmentioning
confidence: 99%
See 1 more Smart Citation